Modelo de negocio para el desarrollo de proyectos de generación distribuida (2020)
The Colombian government's plan aims to strengthen the electric power sector through the implementation of the Advanced Measurement Infrastructure, the Automation of the distribution network, the Distributed Resources and the Electric Vehicles; All this entails a technological and economic challenge, due to the current conditions of the different Colombian municipalities, few will be able to face it. Based on this need, it is proposed to evaluate a business model to encourage the development of distributed generation projects, by supporting the network operator, as a strategic partner, in the activities of updating the electrical network and installation of generation systems with renewable energy. The operator of the electrical power network of the municipality of San José de Guaviare was taken as a case study; the results represent an attraction for the company that provides the public service; because they will be able to meet the goals proposed by the government, improve their indicators and the quality of service provision, without significantly impacting the economy of the population in the area of influence.